2014
DOI: 10.1016/j.actamat.2013.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Origin of {332} twinning in metastable β-Ti alloys

Abstract: In this paper, the origin of {332}<11 3 > twinning, which is a unique twinning mode in metastable -Ti alloys, was investigated. The possible twinning modes in metastable -Ti alloys are derived by considering lattice instability in addition to the theory of the crystallography of deformation twinning. In order to consider lattice instability in the bcc structure, a modulated Acta Materialia, 64 (2014) 345-355. 2 structure was proposed. We then clarify how the modulated structure facilitates the {332}<11 3 > t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(66 citation statements)
references
References 59 publications
2
64
0
Order By: Relevance
“…The change of the mechanisms is due to Mo diffusion induced stability increase with coarsening iso particles. The suppression of {332}<113> twinning owing to the increased stability is well agreed with previous experimental results [11] and a recently proposed model [12]. After further coarsening of the iso phase and the presence of nano phase at 533K aging, deformation mechanisms were therefore largely suppressed, leading to brittleness in tensile test.…”
Section: Microstructure Investigations On Deformed Lta Samplessupporting
confidence: 78%
“…The change of the mechanisms is due to Mo diffusion induced stability increase with coarsening iso particles. The suppression of {332}<113> twinning owing to the increased stability is well agreed with previous experimental results [11] and a recently proposed model [12]. After further coarsening of the iso phase and the presence of nano phase at 533K aging, deformation mechanisms were therefore largely suppressed, leading to brittleness in tensile test.…”
Section: Microstructure Investigations On Deformed Lta Samplessupporting
confidence: 78%
“…According to a recently proposed mechanism, {112}<111> β twinning is the most common for stable bcc structures while {332}<113> β twinning is facilitated by lattice modulation of a destabilized bcc matrix [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another common deformation mechanism is mechanical twinning for β-Ti alloys which have low stacking fault energies [41]. In metastable β-Ti alloys, {112}〈111〉 and {332}〈113〉 twinning system have been reported [42,43].…”
Section: Microstructural Evolution Of β Titanium Alloys In the Procesmentioning
confidence: 99%
“…Several models of the movement of atoms required in {332}〈113〉 twinning have been reported [172,173], and it has been considered that instability of the metastable β-Ti phase allows complex movement of atoms and facilitates {332}〈113〉 twinning [174]. Tobe et al [41] studied {332}〈113〉 twinning and compared it with other twinning modes by taking account of the shear and shuffle mechanisms of the twinning modes, and concluded that lattice instability lowers the possibility of {112}〈111〉 twinning because additional shuffling to form the {112}〈111〉 twins is caused by the lattice modulation. Therefore, {332}〈113〉 twinning of the bcc structure was reported as the most likely twinning mode due to the required lower magnitude of shuffle in comparison with the other twinning modes.…”
Section: Martensitic Transformation and Heat Treatments On  Titaniummentioning
confidence: 99%
See 1 more Smart Citation